Inflation Forecast Errors and Time Variation in Term Premia - Bondt, Werner F. M. De; Bange, Mary M. (Journal of Financial and Quantitative Analysis, 1992)
The expectations theory of the term structure is well known to give wrong signals as to the future course of long-term interest rates. One explanation involves rational time-varying term premia. However, the “anomaly” may also be due to inflation forecast errors. We study survey forecasts of inflation. It seems that the respondents' forecasts are insufficiently adaptive. Interest rates reflect expectations similar to the inflation forecasts. As a result, past survey forecast errors reliably predict premia on U.S. Government Bonds.